Internal structure of amylopectin from the pericarp tissue of developing wheat kernels. Issue 11 (7th September 2015) - Kalinga, Danusha N.; Bertoft, Eric
Abstract : Pericarp starch is a transient starch that forms in the developing wheat kernel and decomposes concurrently with the appearance of the endosperm. The detailed structure of the amylopectin component of pericarp starch granules was investigated and compared with amylopectin from mature wheat endosperm. Clusters of chains from the macromolecule were isolated by hydrolysis with α‐amylase from Bacillus amyloliquefaciens and were then transformed to limit dextrins using phosphorylase and β‐amylase. The pericarp clusters consisted of 14.2 chains on average and had a 16.1% degree of branching, which was similar to the characteristics of clusters from large endosperm starch granules, as was the composition of the branched building blocks. However, the pericarp clusters exhibited a somewhat lower number of the largest building blocks. Other structural attributes, such as the average number of building blocks in the clusters and the length of the interblock segments, were also similar to those of endosperm starch. It is concluded that the cluster structure of wheat pericarp amylopectin essentially matches that of its endosperm counterpart.